The Dynamics of Crowdfunding in a Frontier Market: An Exploratory Research on Romania (European Journal of Marketing and Economics, 2018)
In the last ten years digitalisation has maximised the power of online communities and has created a strong link to directly sustaining and financing innovation. One of the disruptive digital outcomes is crowdfunding which represents an alternative way of financing innovative ideas or projects by raising small amounts of money from a large number of individuals through dedicated online platforms usually using a reward-based model where funders receive something in return for backing a project. A starting point of this study wasa research conducted by Ethan Mollick (2013) on projects initiated on Kickstarter crowdfunding platform between 2009 and 2012 that gives a perspective on the dynamics of success and failure among crowdfunded ventures. In this paper the key findings of the above mentioned study are further developed in the context of the Romanian crowdfunding market by taking into account the level of preparedness when starting a campaign, the number of updates after publishing the prospectus and the type of compelling rewards offered by the issuers as a framework. The database consists of data regarding the projects initiated between 2016-2018 on the top three crowdfunding platforms in Romania. The study delivers insights into the level of development and the understanding of the crowdfunding phenomenon in Romania, describing the ability to get funded or get extra funds and also the main features of the most funded campaign categories. The main chapters of the paper highlight a literature review of the dynamics of crowdfunding, presentation and analysis of data and conclusions regarding changes in the way online communities understand crowdfunding phenomenon and decide to be involved in it.
Keywords: crowdfunding, social investment, online community, social media, mass collaboration, digitalization, financial inclusion